PERBEDAAN PENGARUH PEMBERIAN SUSU KEDELAI DENGAN AKTIVITAS FISIK INTENSITAS SEDANG TERHADAP PENURUNAN BERAT BADAN - BAHDI SATYA PRAWIRA HARAHAP; DEBBY MIRANI LUBIS (LP2MTBM MAKARIOZ, 2023)
Obesity is a condition that exceeds a person's relative body weight. Excess nutrition is not found in urban communities, but also in rural communities. One plant that is thought to be beneficial for weight loss is soybean (Glicine max Mirril) which is usually used in the form of a milk preparation called soy milk. Objective: To see the effect of offering soy milk with intense physical activity for 30 minutes per day on weight loss. This type of experimental research was designed with pre and post test group design with a total sample of 32 people divided into 2 groups (P1 and P2), each treatment group consisting of 16 people. the environment is between the physical activity group and soy milk with p = 0.005. Being in a study that states the group between milk before and after treatment with a value of p = 0.001. The intensity that exists in the friendliness between physical activity before and after treatment with p = 0.006. the effect of offering soybeans and moderate intensity physical activity for 30 minutes on weight loss for the employees of RSU Wira Husada Kisaran.